Inhibition of α-, β-, γ-, δ-, ζ- and η-class carbonic anhydrases from bacteria, fungi, algae, diatoms and protozoans with famotidine - Andrea Angeli; Mariana Pinteala; Stelian S. Maier; Sonia Del Prete; Clemente Capasso; Bogdan C. Simionescu; Claudiu T. Supuran (Taylor & Francis Group, 2019)
Famotidine, an antiulcer drug belonging to the H2 antagonists class of pharmacological agents, was recently shown to potently inhibit human (h) and bacterial carbonic anhydrases (CAs, EC 4.2.1.1). We investigated the inhibitory effects of famotidine against all classes of CAs from the pathogenic bacteria Vibrio cholerae, Burkholderia pseudomallei and Mycobacterium tuberculosis Rv3273 β-CA, as well as the CAs from the nonpathogenic bacteria/cyanobacteria Sulfurihydrogenibium yellowstonensis, S. azorense, Pseudoalteromonas haloplanktis, Colwellia psychrerythraea and Nostoc commune. The δ- and ζ-CAs from the diatom Thalassiosira weissflogii, the fungal enzymes from Cryptococcus neoformans, Candida glabrata and Malassezia globosa, as well as the protozoan enzymes from Trypanosoma cruzi and Plasmodium falciparum, were also investigated. Anopheles gambiae β-CA was also investigated. All these enzymes were effectively inhibited by famotidine, with affinities between the low nanomolar to the micromolar range. The best inhibition was observed against C. glabrata β-CA and TweCAζ, with KIs ranging between 13.6 and 22.1 nM.